Paper, Power, and Procedure: Reflections on Amazonian Appropriations of Bureaucracy and Documents. (14th October 2016) - Allard, Olivier; Walker, Harry
Abstract: The creative and ever‐expanding appropriations of bureaucracy and documents on the part of Amazonian peoples today transcend simple dichotomies between orality and literacy, state and non‐state power, and domination and resistance. The papers collected here highlight the specific forms taken by such engagements and the ways in which they assume a key role in local political processes, offering new perspectives on issues ranging from the everyday workings of the state to local theories of language and materiality. In this introductory essay we draw particular attention to the importance of documents as mediators which facilitate new forms of communication; to the prevalence of bureaucratic magic and ritual; and to the ways in which regional bureaucratic and documentary processes are closely linked to both wealth and violence.